The memorialization of B. Khmelnytsky by means of fine arts in XIX century - Brahina, Tetiana; Brahin, Yu. (My University, 2021)
У статті тезово розкрито відображення в образотворчому мистецтві теми Визвольної війни в Україні середини XVII ст. та її харизматичного лідера Богдана Хмельницького.

The theme of the liberation war in Ukraine in the middle of the seventeenth century and the figure of its charismatic leader Hetman Bohdan Khmelnytsky – in ambiguous interpretations of his activities and heritage – is one of the central themes of fine arts. In the 19th century during the intensification of the processes of nationbuilding grew interest to the person of the creator of the Ukrainian state B. Khmelnytsky.
Keywords: Богдан Хмельницький; меморіалізація історичної пам'яті; memorialization